Diagnosis of the Causes of the Pleural Effusion by Biochemical Parameters - Yamamoto, Masahiko; Asai, Manabu; Hida, Toyoaki; Morishita, Munehiko; Yoshikawa, Kosho; Urata, Atsuo; Takada, Katsutoshi; Sadoh, Satofumi; Torii, Yoshio; Suzuki, Masayuki; Suzuki, Takamoto; Hasegawa, Yasuhiro; et al. (The Japanese journal of thoracic diseases, 1984)
We studied 7 parameters such as adenosine deaminase (ADA), immunosuppressive acidic protein (IAP), carcinoembryonic antigen (CEA), tissue polypeptide antigen (TPA), ferritin, lysozyme (LZM), α-2-HS glycoprotein (AHSG) in 94 pleural effusion. The diagnostic usefulness of measurement of these biochemical parameters was demonstrated. The combination of these parameters elevated the accuracy of biochemical diagnosis. The most effective combination was considered to be ADA, CEA, IAP, and TPA. The combination of ADA, CEA, IAP might also be effective in differential diagnosis. We performed multiple regression analysis for these biochemical parameters and diseases. The score derived from multiple regression analysis was more useful in the differential diagnosis between tuberculous pleurisy and malignant effusion. The most effective combination seemed to be ADA, IAP, CEA, and AHSG. The combination of ADA, CEA, plus IAP or the combination of ADA plus IAP also seemed practical. We introduced a computer-assisted diagnostic system, SHELP which can be used usefully and effectively by means of input of the results of the measurement of these biochemical parameters.